Pengaruh Degradasi Kekakuan Pada Batang Diagonal Tekan Terhadap Kinerja Jembatan Rangka Baja Bentang 60 m. - Ismail Patawe, Mohammad Hamdani; Nur, Kasmat Saleh; Gani, Mirzan (FROPIL (Forum Profesional Teknik Sipil), 2023)
A bridge is an infrastructure built solidly and safely to serve community activities well. In the course of its development, some steel truss bridges suffer a problem which is often caused by a traffic accident, resulting in a degradation of a bridge element. The missing of member can change the structure that will lead to the instability of a bridge if the assumption of joint used is pinned. In contrast, the bridge structure will function as a frame even when an element is missing if the assumption of joint used fixed. This research aimed to find out the effect of stiffness degradation of compressive diagonal member on the performance of a steel truss bridge. To find out the effect , Class A steel truss bridge with a span of 60m constructed by PT. Wiratama GlobalIndo Jaya was selected. The bridge was designed using the SAP 2000 V.18 application with two treatments, namely the pinned the fixed joint. There were three compressive diagonal members that changed its stiffness degradation of 20%, 40%, 60%, and 80% including non-degradation as control. Findings reveal that member number 3 was the most crucial element that reached 4.307% of deflection and 8.65% of stress in the pinned joint. Furthermore, the results showed that the member obtained 4.230% of deflection and 17.87% of stress in the fixed joint. These results signified that the fixed joint provided a lower deflection than the pinned joint. Conversely, the stress on the fixed joint was greater than on the pinned joint